2020
DOI: 10.1021/acs.est.9b07604
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Stable Metal–Organic Framework-Engineered FeS2/C Nanocatalyst for Heterogeneous Electro-Fenton Treatment: Validation in Wastewater at Mild pH

Abstract: Herein, the novel application of FeS2/C nanocomposite as a highly active, stable and recyclable catalyst for heterogeneous electro-Fenton (EF) treatment of organic water pollutants is discussed. The simultaneous carbonization and sulfidation of an iron-based metal organic framework (MOF) yielded well-dispersed pyrite FeS2 nanoparticles of ~100 nm diameter linked to porous carbon. XPS analysis revealed the presence of doping N atoms. EF treatment with an IrO2/air-diffusion cell ensured the complete removal of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(48 citation statements)
references
References 66 publications
2
46
0
Order By: Relevance
“…In addition, CoFe 2 O 4 /MoS 2 exhibits outstanding pH initial adaptability, showing similar phenol degradation performance even at pH initial ≈7 and pH initial ≈9 (Figure 2 b). This result is also considered to be one of the advanced features of this heterogeneous Fenton system compared to traditional homogeneous Fenton systems (Figure S12) [3c] . In our case, when the pH initial of a solution containing pollutants is adjusted to neutral, the addition of CoFe 2 O 4 /MoS 2 causes the pH to approach 3.0–4.0; that is, the acidic nature of the catalyst causes the actual pH to deviate from the predetermined value; however, an excellent degradation rate of pollutants is maintained (Figure 2 c).…”
Section: Resultsmentioning
confidence: 76%
“…In addition, CoFe 2 O 4 /MoS 2 exhibits outstanding pH initial adaptability, showing similar phenol degradation performance even at pH initial ≈7 and pH initial ≈9 (Figure 2 b). This result is also considered to be one of the advanced features of this heterogeneous Fenton system compared to traditional homogeneous Fenton systems (Figure S12) [3c] . In our case, when the pH initial of a solution containing pollutants is adjusted to neutral, the addition of CoFe 2 O 4 /MoS 2 causes the pH to approach 3.0–4.0; that is, the acidic nature of the catalyst causes the actual pH to deviate from the predetermined value; however, an excellent degradation rate of pollutants is maintained (Figure 2 c).…”
Section: Resultsmentioning
confidence: 76%
“…4 The most attractive part is the generation of highly aggressive hydroxyl radicals ( OH, E 0 = 2.80 V/NHE), which have been proved to be one of the most powerful and environment-friendly species to attack organic pollutants. [5][6][7][8] Nevertheless, the widespread use of the Fenton reaction is being limited by its bottleneck problems, including the narrow pH range (pH 2-3) for normal reactions, 9 and the Fe-containing sludge generation due to the rate limitation of electron recycling, 10 which is considered secondary pollution and requires additional treatment processes. To address these problems, various types of heterogeneous Fenton-like materials such as zero-valent transition metals, 11 transition metal oxides, 12,13 supported/doped transition metal solids, [14][15][16] and single atom catalysts 17 were developed.…”
Section: Introductionmentioning
confidence: 99%
“…His results showed that Fe/Fe 3 C@PC outperformed common heterogeneous catalyst such as Fe 0 , Fe 3 O 4 and Fe 2 O 3 . Ye et al [ 82 ] reported the preparation of pyrite NPs linked to porous carbon (Fe 2 S/C) by simultaneous carbonization and sulfidation of Fe-based MOF. Efficient removal of fluoxetine was observed by authors and the enhancement of catalytic activity was confirmed by comparing with natural pyrite and Fe salt.…”
Section: Mofs As Indirect Catalysts For Electrochemical Fenton-like Processesmentioning
confidence: 99%
“…His results showed that Fe/Fe3C@PC outperformed common heterogeneous catalyst such as Fe 0 , Fe3O4 and Fe2O3. Ye et al [82] reported the preparation of pyrite On the other hand, MOF-derived materials can also be used alone as suspended heterogenous catalyst in the solution to activate H 2 O 2 in EF process. Du et al [81] prepared a magnetic NP (Fe/Fe 3 C@PC) using MIL-101(Fe) as precursor by a simple pyrolysis method.…”
Section: Mofs As Indirect Catalysts For Electrochemical Fenton-like Processesmentioning
confidence: 99%